Low Latency Demodulation for High-Frequency Atomic Force Microscopy Probes - Lagrange, Denis; Mauran, Nicolas; Schwab, Lucien; Legrand, Bernard (IEEE transactions on control systems technology, 2021)
One prerequisite for high-speed imaging in dynamic-mode atomic force microscopy (AFM) is the fast demodulation of the probe signal. In this contribution, we present the amplitude and phase estimation method based on the acquisition of four points per oscillation, with the sampling frequency being phase-locked on the probe actuation. The method is implemented on a RedPitaya platform, with its clock being generated from the actuation signal of the probe. Experimental characterizations using square-modulated sine waves show that latency of 500 ns is achieved with a carrier frequency of 10 MHz, which is ten times faster compared with a state-of-the-art lock-in amplifier. A tracking bandwidth greater than 200 kHz is obtained experimentally. The method is eventually applied to a close-loop AFM scan realized using a 15-MHz AFM probe, showing its suitability for high-frequency oscillating probes.